Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To determine which equation can replace [tex]\( 3x + 5y = 59 \)[/tex] in the original system while still producing the same solution, consider the original system of linear equations:
1. [tex]\( 3x + 5y = 59 \)[/tex]
2. [tex]\( 2x - y = -4 \)[/tex]
First, let's manipulate the second equation to align it with the first equation in a way that helps us maintain the solutions' consistency.
Multiply the second equation by 5:
[tex]\[ 5(2x - y) = 5(-4) \][/tex]
Expanding this, we get:
[tex]\[ 10x - 5y = -20 \][/tex]
Now, observe that the equation [tex]\( 10x - 5y = -20 \)[/tex] can serve as a replacement for the original equation [tex]\( 3x + 5y = 59 \)[/tex] while maintaining the solutions' consistency. This new system of equations will now be:
1. [tex]\( 10x - 5y = -20 \)[/tex]
2. [tex]\( 2x - y = -4 \)[/tex]
These two equations will yield the same solutions for [tex]\( x \)[/tex] and [tex]\( y \)[/tex] as the original system.
Therefore, the equivalent equation that can replace [tex]\( 3x + 5y = 59 \)[/tex] is [tex]\( 10x - 5y = -20 \)[/tex]. Hence, the correct option is:
[tex]\[ 10x - 5y = -20 \][/tex]
1. [tex]\( 3x + 5y = 59 \)[/tex]
2. [tex]\( 2x - y = -4 \)[/tex]
First, let's manipulate the second equation to align it with the first equation in a way that helps us maintain the solutions' consistency.
Multiply the second equation by 5:
[tex]\[ 5(2x - y) = 5(-4) \][/tex]
Expanding this, we get:
[tex]\[ 10x - 5y = -20 \][/tex]
Now, observe that the equation [tex]\( 10x - 5y = -20 \)[/tex] can serve as a replacement for the original equation [tex]\( 3x + 5y = 59 \)[/tex] while maintaining the solutions' consistency. This new system of equations will now be:
1. [tex]\( 10x - 5y = -20 \)[/tex]
2. [tex]\( 2x - y = -4 \)[/tex]
These two equations will yield the same solutions for [tex]\( x \)[/tex] and [tex]\( y \)[/tex] as the original system.
Therefore, the equivalent equation that can replace [tex]\( 3x + 5y = 59 \)[/tex] is [tex]\( 10x - 5y = -20 \)[/tex]. Hence, the correct option is:
[tex]\[ 10x - 5y = -20 \][/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.